LOVE AND HATE DEPICTED IN “THE MOTHER” SHORT STORY BY WILLIAM SOMERSET MAUGHAM - Roswita M. Aboe; Rohania Wati Buru (Cakrawala Bahasa, 2021)
This research focuses on the analysis of love and hate in the short story “The Mother” by W. Somerset Maugham. The problem question is: How does the author describe love and hate in this novel. The focus of this research is about love and hate and elements of literature that are built in short stories. As a literary work, this analysis uses a descriptive research design that is used to describe the data based on the findings obtained in statements related to love and hate in short stories. The main data is the short story "The Mother" supported by secondary data obtained from various sources, books, magazines and author biographies. Based on the results of data analysis, it was found that the author described the love in this short story as the love of Eros and Agape. Eros love is described as a relationship due to physical attraction between a man and a woman and vice versa. The main love depicted is the Agape type of love. Although this type of love is a love that does not prioritize itself, it is described as an unusual mother's love for her child. Does not want her child to get another love, but only wants her child for herself. As for hate, the author describes a person's excessive hatred because of his love for his child, the mother becomes hateful, emotional and does not like other people so that the peak of the hatred is realized by taking the lives of others.